Understanding the spatial distribution of crime in hot crime areas. Issue 3 (18th July 2019) - Wang, Zengli; Zhang, Hong
Abstract : Hot crime areas are always targeted for police patrol to deter crimes. While much research has studied the distribution patterns of hot crime areas, research on the spatial distribution of crime within hot crime areas remains limited. Using burglary records in a large Chinese city, the 'hottest' place with the highest crime density was located using two spatial temporal kernel density estimation methods. The results indicated that the majority of crime within hot crime areas was concentrated within a small area distant from the hot area's center. These results provide a micro view of crime distribution within hot crime areas. Our analysis indicates that the results will not be affected by the methods adopted in identification of hot areas. This research is expected to improve the efficiency of police patrols.